(untitled) (Czech Journal of International Relations, 1999)
Private military associations represent a new phenomenon in international relations. Their significance has been rising since the end of the Cold War. The increasing attention devoted to them over the past few years is the result of several factors. First of all, the fact that these are subjects that seek to fill gaps in the market and whose existence is motivated, above all, by the prevailing demand of the market. Private armies to some extent represent the extended arm of the foreign policy of certain countries (especially the US, France, and Great Britain), and enable them to participate in activities in which they otherwise could not or would not be willing to participate. The interconnection between supra-national corporations and private armies is evident. Lately, there have been reflections on the utilization of these associations in peace-keeping operations. We can divide the private military associations into “active” and “passive”. Active associations are engaged also in combat activities whereas the passive are involved merely in training and consultation (logistics, advice in military matters, etc.). In this respect, Executive Outcomes and Sandline International openly take part in combat activities. But even firms that are currently regarded as passive (Military Professional Resources Incorporated, Defence Systems Limited) can rapidly develop such capacities. The impact of these groups has triggered an intense discussion about their role and responsibility. Waging war and ensuring security has traditionally come under the competence of the state and the transfer of these activities into private hands launched a discussion on the positive and negative aspects of private armies in societies on a global scale, on the possibility or impossibility of controlling them and on their responsibility or irresponsibility towards the national government, possibly towards the types of institutions such as the UN. This essay offers a brief historical review of private military associations. It describes the biggest and best-known association operating in this sphere, including its activities. The final section, sums up the discussion to establish to what extent these are merely “mercenaries” and to what extent these associations can be used for the benefit of certain supra-national institutions and operate in peace-keeping missions.